2006
DOI: 10.1590/s1807-59322006000500011
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of the Superficial External Pudendal Artery: A Quantitative Study

Abstract: The importance of the superficial external pudendal artery in cases of lower limb obstructive arteriopathies has been established, and a perfect knowledge of its anatomy is desirable for the creation of successful flaps involving it. However, little information is available on the morphometry of this artery. PURPOSE: In this study, we conducted a quantitative investigation of the superficial external pudendal artery as the basis for skin grafts. METHOD: Twenty-five right and left sides of the inguinal region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
8
0
5
Order By: Relevance
“…L'origine: Dans notre série, toutes les artères pudendales externes ont pour origine l'artère fémorale commune. LA FALCE [ 13 ] confirme cette origine exclusive sur l'artère fémorale commune, à partir d'une série de dissection de 50 régions inguino-fémorales sur des sujets anatomiques. Par contre, une origine au niveau de l'artère fémorale profonde est décrite par deux auteurs.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…L'origine: Dans notre série, toutes les artères pudendales externes ont pour origine l'artère fémorale commune. LA FALCE [ 13 ] confirme cette origine exclusive sur l'artère fémorale commune, à partir d'une série de dissection de 50 régions inguino-fémorales sur des sujets anatomiques. Par contre, une origine au niveau de l'artère fémorale profonde est décrite par deux auteurs.…”
Section: Discussionunclassified
“…Cette prédominance est retrouvée, ailleurs, avec 77% chez les femmes et 63,7% chez les hommes [ 10 ]. Par contre, La Falce [ 13 ] retrouve une artère pudendale externe unique dans 30% de ses 46 régions inguino-fémorales disséquées. Selon le côté, nous notons une légère prédominance droite, chez les patients qui présentent une artère pudendale externe unique.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Superfical external pudendal artery (SEPA) Two studies suggest that this vessel originates from the femoral artery in 98-100% of cases; rarely (0-2%) will it be found as a branch of the profunda femoris Patil et al 1987;La Falce et al 2006). Another anatomic study found that the SEPA has a common origin/trunk with the superficial epigastric artery in 15% of cases.…”
Section: Proximal Branchesmentioning
confidence: 99%